The potential risk factors of cortical visual impairment following cerebral angiography: a retrospective study - Yang Y; Zhang J; Li T (Dove Medical Press, 2019)
Yunna Yang,1 Jing Zhang,2 Tong Li31Department of Neurosurgery, Beijing Chao-Yang Hospital, Capital Medical University, Beijing 100043, People’s Republic of China; 2Department of Neurosurgery, Beijing Friendship Hospital, Capital Medical University, Beijing 100043, People’s Republic of China; 3Department of Interventional Neuroradiology, Beijing Chaoyang Hospital, Capital Medical University, Beijing 100043, People’s Republic of ChinaCorrespondence: Yunna YangDepartment of Neurosurgery, Beijing Chaoyang Hospital, Capital Medical University, No. 5 Jingyuan Road, Shijingshan, Beijing 100043, People’s Republic of ChinaTel +86 105 171 8624Email yangyyn2015@163.comBackground: Cortical visual impairment is an uncommon complication after cerebral angiography with an incidence of 0.3%-1.0%. Here we would like to investigate and discuss the potential risk factors of cortical visual impairment after cerebral angiography.Methods: Based on the presence of post-operative cortical visual impairment, 4,528 patients who received cerebral angiography were split into two groups. The relevant risk factors were compared and analyzed between the groups.Results: In the patient cohort, 11 cases exhibited post-operative cortical visual impairment (0.24%). In particular, seven patients presented with blurred vision and four presented with binocular blindness. Visual sensation of these patients recovered after the treatment. Our univariate analysis revealed that differences in age, weight, sex ratios, proportions of patients with hypertension, diabetes and hyperlipemia, and operation time were not statistically significant between the two groups (P>0.05). The multivariate analysis indicated that the dosage of contrast medium was the independent risk factor for post-operative cortical visual impairment.Conclusion: Clinically, cortical visual impairment following cerebral angiography typically presented as blurred vision or complete blindness. We have identified the dosage of contrast medium as the most critical independent risk factor based on our study. Preventive strategies need to be implemented to avoid post-operative cortical visual impairment in this regard.Keywords: cortical blindness, angiography, contrast agent